Map of the Best Selling Health Products During the Covid-19 Pandemic Period on the Popular Marketplace in Indonesia - Susilawati, Wati; Alamanda, Dini Turipanam; Fajri, Siti Galfanny Rahmanillahi Sabitri; Ramdani, Risma Muhamad (Research Horizon, 2022)
The Covid-19 pandemic can change consumer habits and behavior, consumer preferences regarding health products they buy in the marketplace are increasingly shifting. Health products that became the best-selling products during the pandemic include masks, hand sanitizers, face shields and vitamin C. This study aims to determine the criteria for each health product based on the attributes of health products in popular marketplaces in Indonesia. The research method used is descriptive quantitative with a survey conducted to 100 respondents. The data is then analyzed using a multidimensional scaling approach to produce a map of the best-selling health products on popular marketplaces in Indonesia. The results show that the product that has the most superior rating in various health product attributes is the mask product, followed by vitamin C, face shield and hand sanitizer. This can be seen from the various attributes involved such as efficiency, effectiveness, health benefits, side effects, ingredients, caution, targeting accuracy, product reactions and product durability. This study shows that the attribute value of a product can change along with changes in the environment and consumer needs.